Ranging the Results Achieved in Biomotoric and Specific-Motoric Skills in Handball Players and Non-Athletes Cadet - Aldijana Muratović; Danilo Bojanić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2016)
The goal of research is to establish differences in biomotoric space with young people at the age of cadets (14 ± 6 months; 15 ± 6 months) from Montenegro. The study covers a sample of 500 respondents in total, where 400 of the students are not angaged in organized training process (non-athletes) and 100 are handball players of organized trainings. Biomotoric space is treated with twenty one (21) variables that hypothetically cover the space of: segmented speed, flexibility, explosive leg power, explosive power of arm and shoulder, repetitive power, coordination and balance. The space of specific motoric abilities is tested with five (5) variables that hypotetically cover the space of: shot precision, ball handling capability, slalom running speed, speed in ball control in movement and speed of movement without ball. Data obtained from the tests is calculated on basic statistic approaches. The paper presents the rank of biomotoric and specific-motoric abilities for each group of respondents to the results obtained. The obtained results suggest the following conclusions as most significant: 1) in the space of biomotoric abilities better results achieved the handball players from the Continental region against those of Mediterranien; 2) in specific biomotoric abilities handball players from the Continental region marked better results as against those of the Mediterranien; 3) in biomotoric abilities handball players achieved better results in comparison with the non-athletes; and 4) in specific biomotoric abilities handball players achieved better results in comparison with the non-athletes.